Cellular senescence and other age-related mechanisms in skeletal diseases - Ke Li; Sihan Hu; Hao Chen (Bone Research)
Abstract Cellular senescence and its senescence-associated secretory phenotype (SASP) represent a pivotal role in the development of skeletal diseases. Targeted elimination or rejuvenation of senescent cells has shown potential as a therapeutic strategy to reverse age-related skeletal senescence and promote bone regeneration. Meanwhile, other age-related mechanisms, involving altered cellular functions, impaired intercellular crosstalk, disturbed tissue microenvironment, and decreased regenerative capacity, synergistically contribute to the pathogenesis. In this review, we outline the cellular senescence and other age-related mechanisms in developing skeletal diseases, including osteoporosis, intervertebral disc degeneration, osteoarthritis, rheumatoid arthritis, bone tumors and ankylosing spondylitis, with the aim of comprehensively understanding their detrimental effects on the aged skeleton and screening the potential targets for anti-aging therapy within the skeletal system.